Re-engineering philosophy for limited beings piecewise approximations to reality - Wimsatt, William C. (Harvard University Press, 2007)
"This book offers a philosophy for error-prone humans trying to understand messy systems in the real world. Against eliminative reductionism, Wimsatt pits new perspectives to deal with emerging natural and social complexities. He argues that our philosophy should be rooted in heuristics and models that work in practice, not only in principle. He demonstrates how to do this with an analysis of the strengths, the limits, and a recalibration of our reductionistic and analytic methodologies. Our aims are changed and our philosophy is transfigured in the process."--BOOK JACKET